Kepemimpinan Pendidikan - Syalsa Dwi Aprina; Khalis Salsabila; Nur Andini (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
The purpose of this article is to identify more about educational leadership. This description uses the Descriptive Literature and Qualitative Study approach method with data collection in the form of interviews. Based on the activities that have been carried out that educational leadership is a process of influencing, mobilizing and coordinating individuals in educational organizations / institutions to achieve these educational goals.leadership is important to do and there are certain factors that affect the success of leadership that comes from the leader himself including: knowledge and expertise which is the educational background of a leader, institution or the type of work in which the leader performs the duties of his office, the attitude and personality of the leader, and the personality attitudes of followers. There are seven challenges and obstacles commonly faced by education leaders in general, namely the complexity of leadership tasks, uncertainty and rapid change, complex performance appraisals, community and stakeholder demands, limited resources, cultural and ethnic differences, and time pressures. And educational leadership itself has a very important role to improve the quality of education, create a positive school culture, lead successful educational change, and manage conflict in the school environment.